Predictors of Recurrence of AF in Patients After Radiofrequency Ablation - Iskren Garvanski (Radcliffe Medical Media, 2019)
Catheter ablation is a well-known treatment for patients with AF. Despite the growing knowledge in the field, the identification of predictors of recurrence of AF after catheter ablation is one of the primary goals and is of major importance to improve long-term results of the procedure. The aim of this article is to provide an overview of what has been published in recent years and to summarise the major predictors, helping cardiac electrophysiologists in the selection of the right candidates for catheter ablation.